2017
DOI: 10.1515/ausae-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity study of sorghum (Sorghum bicolor (L.) Moenc) genotypes, Ethiopia

Abstract: Abstract. Sorghum bicolor is one of the most important cereal crops around the world, particularly in Africa, highly cultivated for dietary staple. For this reason, a good knowledge and usage of this genetic resource in sorghum accessions is highly vital for improving crop quality. Analysis of genetic variability among the accessions will enable accurate results in breeding. The research design used was augmented design, which is common in many gene banks. This research finding would be used later by plant bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
2
11
0
1
Order By: Relevance
“…The grouping of accessions in this study which showed indications of local adaptations of sorghum genotypes was in line with the fact that sorghum is a crop plant having broad physiological adaptability to various environments (Badigannavar et al 2018). Moreover, Tesfaye (2017) and Kebbede (2020) underlined that the high genotypic diversity in crop plants is often related to their ability to adapt to various environmental conditions.…”
Section: Genotypic Variability and Relationships Of S Bicolor Accesssupporting
confidence: 81%
See 2 more Smart Citations
“…The grouping of accessions in this study which showed indications of local adaptations of sorghum genotypes was in line with the fact that sorghum is a crop plant having broad physiological adaptability to various environments (Badigannavar et al 2018). Moreover, Tesfaye (2017) and Kebbede (2020) underlined that the high genotypic diversity in crop plants is often related to their ability to adapt to various environmental conditions.…”
Section: Genotypic Variability and Relationships Of S Bicolor Accesssupporting
confidence: 81%
“…In the case of IRAP markers, Tagimanova et al (2015) mentioned that if retrotransposons are considered as neutral components in plant DNA, then retrotransposons are independent of the phenotype. Moreover, the level of genotypic variability is often related to the ability of crop plants to adapt to the environment and the ability to tolerate changes in the environment that might lead to abiotic and biotic stress (Tesfaye et al 2017). In order to find such relationship, Lasky et al (2015) used single nucleotide polymorphism (SNP) variations in sorghum to study the association of SNPs with the environment in predicting phenotypic variations manifested in the form of adaptive traits, and found genomic basis for adaptation to the environment.…”
Section: Genotypic Variability and Relationships Of S Bicolor Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Wood and plant ashes (as with sorghum) are composed of many major and minor elements needed by the plant for growth [61,62]. The motivation of the current study comes from a bio-economy approach, where sorghum (which is unique due to its sugar content, allowing the production of bio-ethanol), after being used for bio-fuel production, is further exploited for chemical compounds in the straw (lignin precursors that can be used as building blocks for bioplastics) [7], and the residue can then be used as biochar or ash for fertilising [23].…”
Section: Sorghum Ash Accelerates Seedling Development In Ricementioning
confidence: 99%
“…Sorghum (Sorghum bicolor L.) is an interesting candidate crop, since it has the ability to grow in P i -poor soil and allows for P i recycling from its straw [5,6]. Sorghum is a multi-purpose economically important crop for food, fodder, bio-fuel, and other industrial uses [7]. In arid and semi-arid areas, sorghum, as a C 4 photosynthetic plant, shows high performance with excellent biomass production within a comparatively short life span [8].…”
Section: Introductionmentioning
confidence: 99%